Structural and magnetic properties of Fe2-xCoSm xO4 - Nanoparticles and Fe2-xCoSm xO4 - PDMS magnetoelastomers as a function of Sm content - Ruiz, Mariano M. (2013)
We have synthesized magnetic Fe2-xCoSmxO4 nanoparticles (NPs) by means of the coprecipitation method, varying Sm content from x=0 to x=0.5. Energy-dispersive X-ray spectroscopy showed agreement between the metal proportion of the obtained nanoparticles and the stoichiometric mixture of cations used for the synthesis. Part of the particles were heated at 800 °C, and both were characterized by X-ray diffraction, scanning electron microscope imaging and magnetization measurements. Physical and magnetic properties were analyzed as a function of Sm content, before and after the heating treatment. A phase segregation is found for the calcined nanoparticles with large Sm content. The magnetic remanence, saturation and coercive field were investigated as a function of Sm content for both heated and unheated (as-prepared) particles. Polydimethylsiloxane-NPs magnetoelastomers were prepared and cured under an external uniform magnetic field, obtaining structured anisotropic composites, in which inorganic needles (columnar micrometric structures) oriented in the direction of the magnetic field are formed. Young modulus and remanent magnetic moment were measured and magnetization time relaxation experiments were performed in the directions parallel and perpendicular to the needles in order to determine the magnetic and elastic anisotropy of the composites. The elastic modulus measured parallel to the needles resulted almost twice in magnitude with respect to the perpendicular modulus. The measured magnetic anisotropy of the composites is probably due to the enhanced interparticle interaction within a needle and the freezing of an preferred easy axis distribution among the particles at the curing process.